Investigating Meteorological Drought in the Northern Region of Nigeria and its Linkage with Climatic Drivers - Olufemi, Afolabi Ayoola; Bamiro, Olufemi Adebisi (International Journal of Disaster Management, 2023)
Drought is a dearth of water, and a recurrence in all regions, but severe in the semi-arid and arid areas with adverse climatic conditions. There have been quite several studies in the country, but fewer in comparison to flood studies, which is in part due to drought nature as a hazard in the region. Drought creeping presence, the prevalence in arid northern Nigeria, and the water deficient problems have spawned the need for this research. The study aims to investigate drought events and drivers using the Standardised Precipitation Index and Standardised Precipitation Evapotranspiration Index for assessing drought historicity, principal component analysis to ascertain the spatiotemporal distribution of rainfall and meteorological drought, in addition to wavelet analysis to determine the relationship with climatic drivers in the region. The region is around latitude 6 N and 14 N and between longitude 2 E and 15 E within the Savanna region of Nigeria covering an area of 729, 815 square kilometers. For analyses, gridded rainfall data was collected from 1951-2021 and processed with a 4-step homogeneity test to track the decline in rainfall and the advent of drought in the region. These analyses showed that drought episodes are a recurring climatic theme in the region, and it was severe in the 1970s, 1980s and continued into the 21st century. Also, principal component analysis and K-means clustering techniques proved that coherence and variation between the regions are a function of the spatial distance between them. Further examination proved that rainfall transits between humid to arid regions, declining in events and intensity as it moves northward of the area. Drought relationship with climatic indices outlines the Tropical South Atlantic as a principal factor with a leading signal of 4-12 months, in the influence of weather conditions, which creates a window in drought management through monitoring.